Early postoperative visual impairments after surgery for tumors of the chiasmal and sellar region and the ways for correcting them (Ukrainian Journal of Ophthalmology, 2025)
Purpose: to assess the frequency of visual function deterioration in the early postoperative period after the removal of tumors of the choroidal and sellar region (CSR), and develop effective treatment methods for postoperative local vasospasm.Material and Methods. We retrospectively reviewed the medical records of 438 patients treated for compressive optic neuropathy due to tumors of the CSR at the Department for Endonasal Cranial Base Endosurgery, SI “Romodanov Neurosurgery Institute, National Academy of Medical Sciences of Ukraine”, in 2018-2024. The main group (group 1) was formed of 33 patients (66 eyes) with postoperative visual deterioration to assess the proposed strategy of treatment for postoperative local vasospasm. The retrospective control group (group 2) was used for comparison and comprised 34 patients (68 eyes) with a similar deterioration who underwent tumor surgery in 2014-2018 and did not receive the restorative treatment. Patients underwent clinical neurological and ophthalmological examinations and neuroimaging and functional studies.Results. We analyzed the outcomes of treatment for postoperative vasospasm which included hemodilution, calcium channel blockers and peripheral vasolidators. In group 1, at day 1 and month 1 after surgery, the mean visual acuity (VA) was 0.44 ± 0.05 and 0.59 ± 0.04, respectively, and the mean mean deviation (MD), -15.34 ± 0.77 dB and -11.51 ± 0.79 dB, respectively (p < 0.05). In group 2, the mean VA improved from 0.38 ± 0.05 to 0.43 ± 0.04, and the mean MD improved from -15.46 ± 0.73 dB to -13.68 ± 0.69 dB, at month 1 compared to day 1 after surgery (p > 0.05). In group 1 and group 2, the mean VA was 0.44 ± 0.05 and 0.38 ± 0.04, respectively, at day 1 after surgery (p > 0.05), and 0.59 ± 0.04 and 0.43 ± 0.04, respectively, at month 1 after surgery (p < 0.05). Additionally, the mean MD was -15.34 ± 0.77 dB and 15.46 ± 0.73 dB, respectively, at day 1 after surgery (p > 0.05), and -11.51 ± 0.79 dB and -13.68 ± 0.69 dB, respectively at month 1 after surgery (p < 0.05).Conclusion. With the proposed therapeutic treatment, VA improved from 0.44 ± 0.05 at day 1 after surgery to 0.59 ± 0.04 at one month after surgery, whereas MD improved from -15.34 ± 0.77 dB to -11.51 ± 0.79 dB (р < 0.05).
Keywords: tumors of the chiasmal and sellar region; compressive optic neuropathy; chiasmal blood supply; endoscopic endonasal surgery for tumors of the chiasmal region; local vasospasm; restorative treatment